Study of Value Losses in Wheat Seed Processing Lines and it’s Economical Assessment - hormoz asadi; Hamid Reza Gazor; Aidin Hamidi; Afshin Eivani (علوم و فناوری بذر ایران)
Objectives of this study, determine value of irrigated wheat seed in waste for processing line, determine of cost and benefit, determine Breakeven price and calculate of economic profitability indices of wheat seed processing lines in Ram Sanat Bahare in Alborz and Akyurek Technology in Kordestan provinces. This research carried out in 2018. Methodology of this study was profitability analysis by Economical engineering methods. According to the results, in Ram Sanat Bahare and Akyurek Technology, the gross value of process in waste of these lines was estimated 4.6 and 2.6 Iranian billion rials, Annual variables costs these lines was calculated 40.94 and 89.75 Iranian billion rials and the total gross value from sales of certifies seeded seeds sold and processed waste determined 55.2 and 104.8 Iranian billion rials, respectively. In Ram Sanat Bahare in Alborz, Breakeven price and gross margin of irrigated bread wheat (Pishgam cultivar) was estimated 14675 Iranian rial per kg and 14 Iranian billion rials, respectively. During (2017-2026), net present value (NPV) this line was 21.8 Iranian billion rials and benefit cost ratio was 1.05. In Akyurek Technology in Kordestan, Breakeven price and gross margin of dry bread wheat (Sardari cultivar) was estimated 17575.2 Iranian rial per kg and 20.34 Iranian billion rials, respectively. During analysis periods, net present value (NPV) this line was 98.7 Iranian billion rials and benefit cost ratio was 1.12. In general, the activity of wheat seed processing companies has been economic.